Technical efficiency of insurance companies: A study of Malaysia / Mohammad Nourani Dargiri - Mohammad Nourani , Dargiri (2017)
The insurance industry in Malaysia has evolved to become less fragmented through deregulation and liberalization reforms. The 2009 liberalization in the form of increased foreign equity participation in the industry, resulted in significant mergers and acquisitions among firms. Yet, there has been no evaluation on the efficiency of insurance companies following the transformational changes in the sector. Further, from a theoretical standpoint, there is inadequate evaluation of the complex service process of the Malaysian insurance business. In this respect the application of the intermediary approach has received little attention in insurance studies. This study therefore focuses on the identification of technical efficiency and its determinants within the Malaysian insurance sector. This study applies a new framework to measure the technical efficiency of insurance companies using a dynamic network data envelopment analysis (DEA), namely the dynamic network slack-based measure. This is followed by a truncated regression analysis with a bootstrapping approach to analyze the internal and external factors driving technical efficiency of Malaysian insurers. The study assembles a new panel dataset of insurance companies, compiled from a range of sources, including insurance reports and firm-level data. The efficiency analysis is broken down according to ownership types (local and foreign insurers) and by business segments (life, general and composite insurers). The data spans the period 2008 to 2014. The qualitative analysis indicates a slow pace of development in the Malaysian insurance industry relative to insurance markets worldwide. In particular the market penetration rate of the life segment in Malaysia has not increased in tandem with the growth of economic activity. The main findings from the DEA analysis suggest that Malaysian insurance companies are 80 per cent efficient in overall terms. The decomposition analysis reveals that the observed inefficiency of insurers is mainly caused by investment capability, which recorded an average 79 per cent level of efficiency relative to premium accumulation whose efficiency level stood at 90 per cent. The results also imply a lack of efficiency among local insurers as compared to their foreign counterparts – largely attributed to a poor investment capability. Further, while composite insurers perform better in the investment capability division, the general segment achieves better efficiency in the premium accumulation division. Overall, the study finds that the 2009 financial liberalization has significantly elevated the efficiency of insurers, including divisional efficiencies. This study broadly supports the use of financial liberalization as a means of promoting technical efficiency of the whole insurance sector, as it directly favors managerial efficiency performance of both foreign and local companies in Malaysia. As such, it indicates to policymakers that precautionary supervision is needed in order to yield further efficiencies in the insurance market. The findings of this study also provide useful insights for insurance companies in terms of resource allocation and strategic decision-making. Local insurance companies need to address the excess usage of inputs and lack of investment capability to improve their position vis-à-vis their foreign counterparts.